Pengaruh Kualitas Produk dan Electronic Word of Mouth terhadap Keputusan Pembelian Produk Skincare Somethinc - Marni Cahyani; Al Ghazali (Jurnal Manajemen Bisnis Digital Terkini, 2024)
The emergence of awareness among Indonesian society regarding the importance of maintaining facial condition has made skincare consumption a trend in shopping. This study aims to investigate the influence of product quality and electronic word of mouth on purchasing decisions for Somethinc skincare products. The population in this study consists of Somethinc skincare users. Purposive sampling was used as the research method, with data collected through distributing questionnaires to 100 respondents and analyzed using SPSS version 26. Hypothesis testing employed multiple linear regression, t-tests (partial), and F-tests (simultaneous). The results of the multiple linear regression yielded the equation Y = 6.624 + 0.278X1 + 0.271X2. The t-test results (partial) indicate a significant influence of product quality on purchasing decisions, with t count (3.672) > t table (1.985), sig 0.000 < 0.05, as well as electronic word of mouth, t count (4.183) > t table (1.985), sig 0.000 < 0.05. The simultaneous F-test resulted in F count (94.601) > F table (3.090), sig 0.000 < 0.05. Somethinc is expected to continue developing products with new formulas while maintaining quality, and to build effective communication by interacting with and responding to consumer reviews.